If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6x+6=2x+-9
We move all terms to the left:
-6x+6-(2x+-9)=0
We add all the numbers together, and all the variables
-6x-(2x-9)+6=0
We get rid of parentheses
-6x-2x+9+6=0
We add all the numbers together, and all the variables
-8x+15=0
We move all terms containing x to the left, all other terms to the right
-8x=-15
x=-15/-8
x=1+7/8
| 7-0.15x=5.55 | | 5=5-5t-2t | | 11x+1=11x+2 | | 8r-5(-2+6r=2(1-7r) | | x+6/7=4/7 | | 5w^2+22w-21=0 | | 4|6-2x|+8=24 | | -2x^2+20x=48 | | 3x-5(x-3)=-6+3x-19 | | 1/4+1/2+h=-3/4 | | 4(3+c)+3=c+4 | | 3(2p-4)=2p-4 | | y=13+7(-1) | | 5=9(10+6t) | | 9c+4-5c=2(c-3) | | -3=x/1 | | 2x+37=-10 | | 10=9(4+3b) | | 5/1+c=5/4 | | 0=-5x^2+10x+15 | | 2(7-4x)-(2x-3)=1-2(x+1) | | n+1.50+2=9.25 | | 8+4w=6(5-2w) | | 5a/8=3/2 | | y/6+5=-13 | | 15/50=9/x | | (5x+35)=75 | | 2-12-3x=10-x+4x | | 2/5r+6=-6 | | 7/8x+1/2=3/16x-4 | | 3x+1=5(x-2)+3 | | 3y+7-5y+6=2y+9 |